Digitizing standard operating procedure to improve employees wellbeing - Sutopo, Y. A.; Polela, Y. A.; Indrianti, Y.; Ahmad, R.; Haryanto, S.; Khan, A. (Man in India Serials Publications, 2024)
Indexed by SCOPUS